The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.12968/jowc.2019.28.8.527
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension at emergency department admission and hospital-acquired pressure ulcers in older patients: prospective study

Abstract: Objective:To investigate the relationship between admission hypotension and hospital acquired pressure ulcers (PU) among older patients in an emergency department.Methods:The study was a prospective cohort conducted between March and May 2017 in the emergency department of a tertiary care hospital in Eastern China. Data on PUs and possible PU risk factors were collected using a pre-designed form. Multivariate logistic regression was used to calculate the adjusted odds ratio (OR).Results:A total of 157 older pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
2
1
3
Order By: Relevance
“…The results of this study showed that the incidence of PI in 13,064 older inpatients was 0.20%, which was lower than the results of domestic and foreign similar studies (Baumgarten et al, 2006; Gong et al, 2019; Wang & Wu, 2008). The incidence of PI in patients aged 80 years or older was the highest, up to 0.95%, lower than 1.34% of Jiang et al's research results (Q. X. Jiang et al, 2023).…”
Section: Discussioncontrasting
confidence: 69%
“…The results of this study showed that the incidence of PI in 13,064 older inpatients was 0.20%, which was lower than the results of domestic and foreign similar studies (Baumgarten et al, 2006; Gong et al, 2019; Wang & Wu, 2008). The incidence of PI in patients aged 80 years or older was the highest, up to 0.95%, lower than 1.34% of Jiang et al's research results (Q. X. Jiang et al, 2023).…”
Section: Discussioncontrasting
confidence: 69%
“…Outros estudos obtiveram resultados semelhantes, como por exemplo Soares et al (2022), no qual a taxa de incidência de UP (numa amostra de doentes em SE) foi de 9,3%. Na pesquisa realizada por Gong et al (2019), a incidência de UP foi de 8,3%, também com uma amostra de doentes admitidos em SE.…”
Section: Discussionunclassified
“…As pessoas com UP têm, geralmente, um período de recuperação prolongado, causam uma dor significativa aos doentes e o seu tratamento conduz a elevados custos para o sistema de saúde. As UP podem conduzir a complicações na pessoa, como por exemplo celulite, artrite séptica e sépsis, incrementando a taxa de morbilidade e mortalidade (Gong et al, 2019;Headlam & Illsley, 2020).…”
Section: Introductionunclassified
“…Considering the delays caused by the handover and the uncertainty of tra c conditions, the time patients spend in ambulances could be much longer. However, during the literature search, we found many Chinese studies on pressure injuries in inpatients and emergency department period (Gong et al, 2019;Jiang et al, 2021;Wei et al, 2021;Zhang et al, 2021), but fail to nd out a study on MDRPI in ambulance transfers. We hypothesize that several MDRPI occurs during ambulance transfers that are incorrectly identi ed as occurring in the emergency department period and lead to statistical errors.…”
Section: Introductionmentioning
confidence: 95%